Cognitive impairment and elevated peripheral cytokines in breast cancer patients receiving chemotherapy - Khan, Mohd Ashif; Bhurani, Dinesh; Hoda, Ubedul; Sehar, Nouroz; Agarwal, Nidhi (Arquivos de Neuro-Psiquiatria, 2022)
Background Anthracyclines-based regimen (5-fluorouracil, doxorubicin, and cyclophosphamide (FAC); cyclophosphamide, epirubicin, and 5-fluorouracil [CEF]) and non-anthracycline based regimens (cyclophosphamide, methotrexate, and 5-fluorouracil [CMF]) are widely used as neoadjuvant chemotherapy for breast cancer patients.Objective The present study was conducted to observe the effects of FAC, CEF, and CMF regimen on cognition and circulatory proinflammatory cytokines (interleukin 6 [IL-6] and interleukin 1β [IL-1β]) for the duration of three cycles of chemotherapy in breast cancer patients.Methods Eighty newly diagnosed HER-2 negative breast cancer patients were enrolled and divided into 3 groups as FAC- (n = 27), CEF- (n = 26), and CMF- (n = 27) receiving patients. Serum IL-6 and IL-1β levels were measured by using enzyme-linked immunosorbent assay (ELISA), and cognition was assessed using the Mini-Mental State examination (MMSE) questionnaire.Results Anthracycline-based regimen was found to increase the levels of IL-6, IL-1β, and decreased MMSE scores compared with CMF regimen (p < 0.05).Conclusion Anthracycline-based regimen caused comparatively higher peripheral inflammation, which could be the reason for more decline in cognition in anthracycline-receiving patients than non-anthracycline group.
Keywords: Cognitive Dysfunction; Mental Status and Dementia; Tests; Breast Neoplasms; Neoadjuvant Therapy; Cytokines